Laboratory analysis to determine the accurate characteristics of urban food waste - A. Charkhestani; D. Yousefi Kebria (Global Journal of Environmental Science and Management)
BACKGROUND AND OBJECTIVES: Although the characteristics food waste have been well studied, some of the problems associated with result reporting have not been addressed. The related data are usually reported by referring to the global statistics, using the empirical models, and performing the laboratory analysis. The aims of the current study were to analyze the municipal food waste characteristics (including physical, proximate, ultimate and heating value analysis), monitor the differences among the laboratory methods, and highlight the significant differences among the food waste characteristics more accurately.METHODS: Sampling was performed weekly at a disposal site located in Sari, Mazandaran, Iran. Food waste was extracted from the municipal solid waste samples. Moisture content, pH, organic matter, ash content, organic carbon, carbon to nitrogen ratio, low heating value and chemical equation of the waste were determined and compared by statistical indices.FINDINGS: The results showed no significant difference between proximate analysis and global statistics for sampling including organic matter and moisture content. In ultimate analysis, statistical investigation of the laboratory results showed that Walkley and black, Kjeldahl, and dry ashing/ion chromatography methods had more accuracy compared to determination by elemental analyzer which puts direct impact on extracted chemical equation. In addition, heating value investigation by empirical models based on proximate analysis (13.6 MJ/kg) was closer to the bomb calorimeter results (13.4 MJ/kg) in average. However, the models developed based on ultimate analysis, including Dulong, Steuer, and Scheurer-Kestner, had a lower accuracy (with higher heating value of 1.4 to 5 MJ/kg). Surveying the reliable sources highlighted the gap in extracted chemical equation and heating value of the food waste with real amount. These findings provided appropriate information about solid waste management and characterization.CONCLUSION: Investigation of the gap among laboratory methods revealed that determination method was a key factor in accurate characterization of food waste. Thus, without using the most accurate laboratory methods, the implementation of waste management plans would face major problems.